The use of the nursing process as a support tool for the child's care for domiciliary care (Research, Society and Development, 2018)
This study aims to share the experience in the use of the Nursing Process as a support tool for child care in home care. It is a descriptive study, having as a participant a child and his family, who were accompanied at home by a nurse during a few months of the year 2018, thus collecting the data. The results of the study were compiled confirme provides for the Nursing Process, following the steps of History and Physical Examination, Nursing Diagnostics, Prescription or Care Plan, Care Implementation and Nursing Assistance Evaluation. It was considered that the realization of this process saw the collection of effective data about the family, thus leading to a comprehensive and long-term care plan. This study has importance in demonstrating the effective use of the Nursing Process at home, leading to a growing contemporary demand.